“I Would be More of a Liability than an Asset”: Navigating the Workplace as a Younger Person with Arthritis - Berkovic, D.; Ayton, D.; Briggs, Andrew; Ackerman, I.N. (SPRINGER/PLENUM PUBLISHERS, 2020)
Purpose Over half the population in Australia with arthritis and other musculoskeletal conditions is aged 25–64 years. This reflects the peak income-earning years for most, yet little research has examined the influence of arthritis on work issues specific to younger people. The aim of this research was to examine the work-related experiences of younger people (defined as those aged 18–50 years). Methods A qualitative exploratory design was used. Participants with inflammatory arthritis or osteoarthritis were recruited from the community, including urban and rural settings. An interview guide was based on the World Health Organization’s International Classification of Functioning, Disability and Health. Deductive and inductive coding techniques were used to identify emerging work-related themes from the data. Results Semi-structured interviews were conducted with 21 younger people (90% female) with a mix of arthritis conditions, vocational backgrounds and career stages. Three themes were identified: (1) the perceived impacts of arthritis on career trajectories, (2) the impacts of arthritis on participants’ workplace environment, employers, and colleagues, and (3) the personal toll of working with arthritis. The personal toll of working with arthritis relates to the arthritis-attributable impacts of physical and psychological symptoms on productivity and presenteeism in the workplace. Conclusion Younger people with arthritis experience numerous challenges at key stages of their careers, from career planning through to productive working. This can be used to inform workplace accommodations for people with arthritis and increase awareness of likely barriers to work productivity among colleagues, employers and clinicians.